2016
DOI: 10.1111/apt.13788
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: the effects of a multispecies probiotic vs. placebo on innate immune function, bacterial translocation and gut permeability in patients with cirrhosis

Abstract: SummaryBackgroundProbiotics may correct intestinal dysbiosis and proinflammatory conditions in patients with liver cirrhosis.AimTo test the effects of a multispecies probiotic on innate immune function, bacterial translocation and gut permeability.MethodsIn a randomised, double blind, placebo‐controlled study, stable cirrhotic out‐patients either received a daily dose of a probiotic powder containing eight different bacterial strains (Ecologic Barrier, Winclove, Amsterdam, The Netherlands) (n = 44) or a placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 41 publications
7
105
0
Order By: Relevance
“…(38,39) This finding has also been reported in models of experimental cirrhosis, in which several probiotics improved the intestinal barrier, decreased bacterial translocation, and ameliorated the proinflammatory state. (40,41) However, in the study by Horvath et al (37) in patients with cirrhosis treated with a different probiotic mixture, the authors did not observe any significant effect on gut permeability, as assessed by a panel of markers including lactulose/ mannitol ratio and fecal zonulin, or inflammatory biomarkers. Liu et al (42) evaluated patients undergoing colorectal surgery treated with a three-strain probiotic and reported a decrease in serum zonulin, a parameter that was unchanged in our study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(38,39) This finding has also been reported in models of experimental cirrhosis, in which several probiotics improved the intestinal barrier, decreased bacterial translocation, and ameliorated the proinflammatory state. (40,41) However, in the study by Horvath et al (37) in patients with cirrhosis treated with a different probiotic mixture, the authors did not observe any significant effect on gut permeability, as assessed by a panel of markers including lactulose/ mannitol ratio and fecal zonulin, or inflammatory biomarkers. Liu et al (42) evaluated patients undergoing colorectal surgery treated with a three-strain probiotic and reported a decrease in serum zonulin, a parameter that was unchanged in our study.…”
Section: Discussionmentioning
confidence: 91%
“…This effect was probably a consequence of an improvement in pathological bacterial translocation, as suggested by the decrease in the neutrophil toll-like receptor 4 expression after stimulation with endotoxin in patients treated with the probiotic. (36) In a more recent study, Horvath et al (37) reported that treatment with a different multispecies probiotic in outpatients with cirrhosis produced an immune modulation consisting of an increase in neutrophil resting oxidative burst and serum neopterin, a marker of macrophage activation.…”
Section: Discussionmentioning
confidence: 99%
“…We included faecal 16S microbiome sequencing data from cirrhotic patients recruited at the outpatient clinic of the Department of Gastroenterology and Hepatology, University Hospital of Graz, Austria who were screened for an intervention study between July 2012 and September 2013 in this post‐hoc analysis. All patients gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme linked immunosorbent assay were used to measure calprotectin, zonulin and serum DAO (Immundiagnostic AG, Bensheim, Germany), as well as LBP and sCD14 (Hycult biotechnology, Uden, the Netherlands). sCD163 and sMR in plasma samples were measured by an in‐house sandwich ELISA using a BEP‐2000 ELISA‐analyser (Dade Behring) as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation